Penyuluhan Hukum Undang-Undang Nomor 11 Tahun 2020 Tentang Cipta Kerja Kepada Milenial dan Pelaku Usaha Mikro Kecil Menengah - Sandy Victor Hukunala (Faculty of Law, Universitas Pattimura, 2022)
Introduction: The COVID-19 pandemic has had a negative impact on the business world and the world of work. A shattered economy and massive layoffs are serious problems. Law Number 11 of 2020 concerning Job Creation is here to answer that challenge. With a focus on simplifying regulations so that investment and the business world can develop which of course has an impact on employment.Purposes of Devotion: The purpose of this service is to provide legal understanding and awareness to the millennial generation who are the active workforce and the majority of Micro Small Medium Enterprises actors today regarding the convenience, protection and empowerment provided by the government through Law Number 11 of 2020 so as to rediscover enthusiasm and confidence in the business world and work. Method of Devotion: The method used in this service is the educational method, namely conducting legal counseling regarding the substance of Law Number 11 of 2022 concerning Job Creation and several derivative rules or their implementation.Results of the Devotion: This legal counseling activity had a positive impact on the millennial generation and Micro Small Medium Enterprises actors in the Small Hative Village who had the opportunity to attend. This can be seen from the active response through the questions asked by the counseling participants. So we hope that understanding this legal counseling material can not only foster enthusiasm and motivation for participants but also raise awareness and legal culture which can later be implemented in the business world and the world of work.